Condicionamento fisiológico e armazenamento de sementes de girassol - Faria, Gabrielle de (2015)
The priming of seeds is a technique that foccus at recovering the membrane system and propitiates a greater uniformity and speed of germination of the samples. Regarding the storage of seeds osmotically conditioned, the concern is to maintain the physiological quality and the seeds conditioned after storage to increase the physiological quality. This study aimed to verify the physiological performance of sunflower seeds conditioned prior to storage and also when conditioned after storage. The study was conducted at the Seed Center Laboratory and Laboratory Oils, Fats and Biodiesel Federal University of Lavras and sunflowers seeds hybrid 251 produced by Heliagro Agricultura e Pecuária LTDA were used. In experiment 1 were repeated seven solutions with and without gibberellic acid (500 ppm) for priming: Ascorbic acid (75 mg L-1), Sucrose (75 mg L-1), Tocopherol (0.1930 ml L-1) ascorbic acid (75 mg L-1) + Sucrose (75 mg L-1), ascorbic acid (75 mg L-1) + Tocopherol (0.1930 ml L-1), Sucrose (75 mg L-1) + Tocopherol (0.1930 ml L-1) and ascorbic acid (75 mg L-1) + Sucrose (75 mg L-1) + Tocopherol. After conditioning the seeds were dried at 35 ° C for 24 hours and stored in multiwall paper bags in cold chamber for 45 days. Germi nation tests, emerging, emerging speed rate and electrical conductivity were performed every 15 days. In experiment 2, the seeds were stored in multiwall paper bags in the cold chamber for a period of up to eight months. Every four months, the seeds were submerged in the same seven solutions used on the first experiment with and without gibberellic acid (500 ppm) for priming. After conditioning the seeds were dried at 35 ° C for 24 hours and performed the physiological testing: germination, emerging, emerging speed index and electrical conductivity. It is concluded in this study that the use of gibberellic acid in the conditioning solutions provided positive effect on the quality of seeds, priming before storage improved the quality of seeds stored for 15 days and the effect of the conditioning was continued until the 30th day of storage. For the seeds conditioned after storage, it was found improved physiological quality in four seasons and eight months of storage.